Мобільні електронні пристрої: можливості використання в освітньому процесі - Козлакова Галина; Kozlakova Galina (Вид. ТОВ «Нілан – ЛТД», 2018)
Резюме. У даній статті автором представлено аналіз мобільних е-пристроїв (ноутбук, планшет, смартфон), особливості їх призначення та використання у педагогічній діяльності та навчанні. Звернено увагу на переваги подання за їх допомогою навчальної інформації та можливий негативний вплив на учнів. Наведено результати анкетування студентів щодо застосування мобільних електронних пристроїв (МЕП). Обговорюється структура відповідного спецкурсу для студентів педагогічних спеціальностей. З’ясовано, що сучасний стан розвитку інформаційно-комунікаційних технологій (ІКТ) дозволяє обходитись без стаціонарного комп’ютера, бо він вимагає обов’язкової присутності на робочому місці, потребує окремого догляду та окремого столу для його розміщення. Визначено, що фахівці давно надали перевагу і успішно працюють із переносними мобільними моделями персональних комп’ютерів (ПК), можливостей яких достатньо для розв’язання різноманітних складних задач, а крім того їх можна перевозити із собою.

Abstract. In this article the author presents an analysis of mobile edevices (laptop, tablet, smartphone), features of their purpose and use in teaching and learning. The attention is drawn to the benefits of providing instructional information with them and the possible negative impact on students. The results of student questionnaires on the use of mobile electronic devices (MEP) are presented. The structure of the corresponding special course for students of pedagogical specialties is discussed. It is revealed that the current state of the development of information and communication technologies (ICTs) allows you to get around without a stationary computer, because it requires a mandatory presence in the workplace, requires separate care and a separate table for its placement. It has been determined that specialists have long been privileged and successfully work with portable mobile models of personal computers (PCs), the capabilities of which are sufficient for solving various complex problems, and in addition they can be transported with them. The author has proved that the advancement of a new wave of mobile electronic technology causes and becomes the cause of new behavior, new social relationships between schoolchildren and parents, students and teachers, which requires: mastering of new technical and programmatic capabilities of this technique; knowledge of the features of mobile operating systems iOS and Android; the development of new methodological approaches to its study and daily use without prejudice to the physical and social status of individual students, students and the collective as a whole.

Резюме. В данной статье автором представлен анализ мобильных е-устройств (ноутбук, планшет, смартфон), особенности их назначения и использования в педагогической деятельности и учебе. Обращено внимание на преимуществах представления с их помощью учебной информации и возможное негативное воздействие на учащихся. Приведены результаты анкетирования студентов по применению мобильных электронных устройств (МЭП). Обсуждается структура соответствующего спецкурса для студентов педагогических специальностей. Выяснено, что современное состояние развития информационно-коммуникационных технологий (ИКТ) позволяет обходиться без стационарного компьютера, так как он требует обязательного присутствия на рабочем месте, требует отдельного ухода и отдельного стола для его размещения. Определено, что специалисты давно отдали предпочтение и успешно работают с переносными мобильными моделями персональных компьютеров (ПК), возможностей которых достаточно для решения различных сложных задач, а кроме того их можно перевозить с собой.
Мобильные электронные устройства: возможности использования в учебном процессе
http://eprints.zu.edu.ua/29150/
Keywords: мобільні електронні пристрої; освітній процес; навчальні заклади; е-платформи; mobile electronic instruments; educational process; universities; electronic platform; мобильные электронные устройства; учебный процесс; учебные заведения; е-платформы